RISK FACTORS FOR POSTOPERATIVE COMPLICATIONS AFTER LAPAROSCOPIC CHOLECYSTECTOMY - Abdurakhmanov, F.M.; Muzaffarov, N.S. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Laparoscopic cholecystectomy is currently considered one of the important approaches to the treatment of acute calculous cholecystitis in elderly and senile patients. According to the terms of the Tokyo Guidelines of 2018, laparoscopic cholecystectomy in elderly and senile patients should be performed immediately after establishing the general condition of the patient as mild or moderate severity. According to the Tokyo Guidelines of 2018, such a condition of the patient of elderly and senile age can be assessed as capable of tolerating laparoscopic cholecystectomy. This review article is devoted to the analysis of the current literature on risk factors for postoperative complications after laparoscopic cholecystectomy in elderly and senile patients.